Determinants Of Organizational Citizenship Behavior In ASN Employees Of The Personnel And Human Resource Development Agency - Nalvin, Mahiya Anjani; Nirwana , Dilla; Yomeini Margareth S; Cia Cai Cen (Jurnal Ekonomi, 2024)
This study aims to determine the effect of work environment on Organizational Citizenship Behavior, work motivation on Organizational Citizenship Behavior and job satisfaction on Organizational Citizenship Behavior in ASN BKPSDM employees of Tebing Tinggi City. The implication of this research is the lack of work motivation in BKPSDM employees, so that it cannot increase optimal Organizational Citizenship Behavior in employees. This research method uses a quantitative approach. The population in this study were all ASN employees of the Tebing Tinggi City Civil Service and Human Resources Development Agency. The sample was taken using the total sampling technique (census) method of 30 ASN employees. Research data obtained through primary and secondary data with data collection through questionnaires, then analyzed using SEM analysis with the help of SmartPLS. The results of this study indicate that work environment has a significant effect on organizational citizenship behavior, work motivation has a positive effect on organizational citizenship behavior, and job satisfaction has a positive effect on organizational citizenship behavior. It is hoped that in the future it is expected to be a guiding material for organizational leaders, especially the government in managing the increase in OCB in the state civil apparatus or ASN.